Determination of antibiotic sensitivities by the Sensititre system. Issue 6 (June 1978) - Phillips, I; Warren, C; Waterworth, P M
Abstract : The Sensititre system provides antibiotics dried in microtitre trays in appropriate concentrations for the determination of minimum inhibitory concentrations (MIC) when organisms are added in liquid culture medium and incubated overnight. Results with a variety of media--for Gram-negative bacilli tested with ampicillin, carbenicillin, cephaloridine, and gentamicin, staphylococci with penicillin, cloxacillin, fusidic acid, and gentamicin, and streptococci with penicillin, ampicillin, cephaloridine, and erythromycin--were usually very similar to those of agar dilution tests. Discrepant results are found in a few situations, and in some cases, especially those involving borderline resistance to fusidic acid and gentamicin among staphylococci and Gram-negative bacilli, we have been unable to suggest modfication to produce the right results. Despite these problems, fortunately few and identifiable, we recommend the system especially for use in laboratories that determine the MICs infrequently.